A criminological internet 'sting'. Experimental evidence of illegal and deviant visits to a website trap - Demetriou, Christina (The British journal of criminology, 2003)
While considerable concerns have been raised about crime and deviancy on the Internet, relatively little research has looked closely at the subject. This paper describes a study on criminal and deviant behaviour that occurred on a World Wide Web site. The Cyber Magpie website was established to determine whether people who visited for the purposes of gaining access to legal material would also attempt to access illegal and/or pornographic material. Over an 88-day period 803 visitors entered the site. By using a tracking facility, it was found that those sections offering illegal and/or deviant material were accessed by a majority of visitors. These findings are discussed in terms of deindividuation theory and with regard to the implications for understanding deviant behaviour in cyberspace